Collaboration of Districts in Fulfilling Rajangan Madura Tobacco National Production - Dzikrillah Thoriqur Rahman; Retno Sunu Astuti (Jurnal Administrasi Publik (Public Administration Journal), 2021)
This study aims to analyze the concept of collaboration between districts in fulfilling the national production of Rajangan Madura tobacco national and to know the factors causing the decline in Rajangan Madura tobacco production. The problems are focused on the decline in tobacco production and the area of agricultural land in each district, and the instability of the price of tobacco which causes anxiety for farmers. The production and area of Madura tobacco farming land has decreased since 2013 with the production produced is only 3.5 tons with an area of 8.4 ha. If the accumulated decline in production and the area of tobacco farming land per year has decreased by 15%of the total normal production per year as much as 29 thousand tons from a land area of 32 hectares in each district.To approach this problem, Wright's theoretical reference was used, there were five key elements in the implementation of intergovernmental relations, namely 1) the roles of government, 2) the interactions of public officials, 3) sustainability communication, 4) the roles administrators, and 5) focus attentions on the policy. The data were collected through observation and literature study and analyzed qualitatively and descriptively. This study concluded that collaboration between districts has shown good cooperation by dividing the roles and tasks of each region. The interaction of public officials had shown cooperation in behavior, beliefs, perceptions and preferences. With regard to the communication that was built from the four regions, looking for ways and solutions to increase Madura tobacco production and prevent instability in the price of Madurese tobacco in the harvest season. This collaboration had a target of achieving the fulfillment of Rajangan Madura tobacco production to increase by thirty percent, namely the production of Madura tobacco in each year was targeted at eighty tons. Three factors caused the decline in Rajangan Madura tobacco production, namely, first, the decline in tobacco prices was a major factor for farmers in producing tobacco. Second, climatic factors also influenced the maturation process of tobacco until it wasready for harvest. Third, the reduction of land owned by the government and the community due to the fulfillment of development in the infrastructure sector.Â